2011
DOI: 10.5194/acp-11-6721-2011
|View full text |Cite
|
Sign up to set email alerts
|

Iodine monoxide at a clean marine coastal site: observations of high frequency variations and inhomogeneous distributions

Abstract: Abstract. The first in situ point observations of iodine monoxide (IO) at a clean marine site were made using a laser-induced fluorescence instrument deployed at Mace Head, Ireland in August 2007. IO mixing ratios of up to 49.8 pptv (equivalent to pmol mol −1 ; 1 s average) were observed at day-time low tide, well in excess of previous observed spatially-averaged maxima. A strong anti-correlation of IO mixing ratios with tide height was evident and the high time resolution of the observations showed IO peaked … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 49 publications
5
26
1
Order By: Relevance
“…Both studies are providing strong evidence that, in contrast to coastal regions where iodocarbon emissions of macroalgae are likely the major source for iodine (e.g. Seitz et al, 2010;Commane et al, 2011), in the open ocean direct marine emissions of inorganic iodine (here assumed to be I 2 ) are important as a source of reactive iodine in the MBL, in line with recent findings of Carpenter et al (2013). This conclusion is corroborated by the following findings of our study:…”
Section: Discussionsupporting
confidence: 92%
“…Both studies are providing strong evidence that, in contrast to coastal regions where iodocarbon emissions of macroalgae are likely the major source for iodine (e.g. Seitz et al, 2010;Commane et al, 2011), in the open ocean direct marine emissions of inorganic iodine (here assumed to be I 2 ) are important as a source of reactive iodine in the MBL, in line with recent findings of Carpenter et al (2013). This conclusion is corroborated by the following findings of our study:…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous measurements of IO at Mace Head which showed maximum levels up to 5 pptv (Saiz-Lopez et al, 2006;Alicke et al, 1999). However, other measurements taken over "hot spots" of exposed seaweed beds have shown IO peak values of up to 50 pptv (Commane et al, 2011). Thus, it can be concluded that the observed background signal could be explained by the presence of IO that would nevertheless not contribute to atmospheric SO 2 oxidation because of a too small IO + SO 2 rate constant.…”
Section: Could X Be a Criegee Radical Produced From Ozonolysis?supporting
confidence: 80%
“…Observations of BrO and IO radicals within the MBL have demonstrated widespread impacts on atmospheric composition and chemistry (Alicke et al, 1999;Sander et al, 2003;Leser et al, 2003;Saiz-Lopez and Plane, 2004;SaizLopez et al, 2004SaizLopez et al, , 2006Peters et al, 2005;Whalley et al, 2007;Mahajan et al, 2010a;Commane et al, 2011;Dix et al, 2013;Gomez Martin et al, 2013;Le Breton et al, 2017), including significant effects on HO x concentrations and on the HO 2 : OH ratio in coastal and marine locations (Bloss et al, 2005a(Bloss et al, , 2010Sommariva et al, 2006;Kanaya et al, 2007;Whalley et al, 2010).…”
Section: Introductionmentioning
confidence: 99%